กรอบการวิเคราะห์ระดับการให้บริการของสายทางที่เหมาะสมในแต่ละยุทธศาสตร์ - ชานนท์ อมรชัยศักดา (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
At present, the Thai government’s budget for road network maintenance is allocated corresponding to road strategies and in line with the national development policy. The determination of road serviceability level target index is an important factor in the system of road network maintenance management because the index will be used to assess the effectiveness of the system. In the past, the average serviceability target level was determined by the experts from the Department of Highways and the Department of Rural Roads. However, since different roads may serve different service purposes, the determination of the serviceability level should correspond with each road strategy. The aim of this research is to present an analytical framework of road serviceability level corresponding to road strategies by using the International Roughness Index (IRI) as a representative index of serviceability level. The findings show that there are three approaches to determine the target IRI which are (1) the road users’ satisfaction approach which is suitable for roads facilitating the several travellers; (2) the economic analysis approach which is suitable for road that accommodate high traffic volume; (3) the minimum life cycle maintenance cost approach which is suitable for service roads or road that are designed to facilitate governmental missions. These three approaches can be considered together in order to determine the appropriate IRI for roads that serve various purposes. This research has provided road network management authorities with an analytical framework that can be applied to be used as a tool to determine the target index in a systematic and appropriate way. In doing so, they will be able to optimize the allocated budget and manage the road network system in line with the national strategy of the government.